1992
DOI: 10.2337/diacare.15.4.559
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Secondary Attack Rate of IDDM to Siblings of Probands Through Older Ages: Pittsburgh Etiology of IDDM Study

Abstract: Males have a greater secondary attack rate of IDDM at older ages than females. This may be due to an increased exposure to environmental agents among males or protective influences operating among females.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
6
4

Year Published

1994
1994
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 13 publications
6
6
4
Order By: Relevance
“…However, a recent large European ecological study has suggested that the incidence of type 1 diabetes and the prevalence in siblings at the time of the diagnosis of a diabetic child are correlated (6). Our estimates of the recurrence risk confirm the finding that brothers are more commonly affected with type 1 diabetes after puberty than sisters (7,27). Furthermore, we found that young-onset diabetes in fathers was associated with increased risk of type 1 diabetes in siblings, which is in keeping with data…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, a recent large European ecological study has suggested that the incidence of type 1 diabetes and the prevalence in siblings at the time of the diagnosis of a diabetic child are correlated (6). Our estimates of the recurrence risk confirm the finding that brothers are more commonly affected with type 1 diabetes after puberty than sisters (7,27). Furthermore, we found that young-onset diabetes in fathers was associated with increased risk of type 1 diabetes in siblings, which is in keeping with data…”
Section: Discussionsupporting
confidence: 90%
“…The cumulative incidence for type 1 diabetes in siblings of type 1 diabetic patients by age 30 years observed in this study, 5.5% on average, is similar to that of most studies where the estimate has varied from 4.9 to 6.4% (2,(7)(8)(9)11). In general, the risk of type 1 diabetes for close relatives is usually quite similar (25,26).…”
Section: Discussionsupporting
confidence: 85%
“…We found the recurrence risk of IDDM in the families of the study population to be higher than hitherto reported from most studies [13,14,[31][32][33] but comparable to the high value of a recent report from Allen et al [19]. The cumulative recurrence risk of siblings at age 60 years was estimated to 9.6 % and interestingly, we also found that the recurrence risk in siblings was significant even after age 30 years (3.2 % from 30 to 60 years).…”
Section: Discussionsupporting
confidence: 86%
“…We found that the probands in the present study were older at the time of diagnosis (22 years) compared to other studies [12,13,15,19,21,23,24,30,33]. One obvious reason might be the inclusion criteria.…”
Section: Discussioncontrasting
confidence: 56%
“…More recently, population-based data have become available, and fairly consistent prevalence rates of 11-13% for the presence of an affected first-degree relative have been reported in subjects with IDDM at the time of diagnosis (6)(7)(8). The risk of IDDM in siblings of diabetic probands up to the age of 30 yr has been estimated to be ‫ف‬ 6-7% (9)(10)(11)(12), although a higher long-term risk, 9.6% up to the age of 60 yr, has been reported recently in Denmark (12). Approximately 4% of the parents of IDDM patients (6,7,10) and 5% of the offspring are affected by the disease (1,13).…”
Section: Introductionmentioning
confidence: 96%